A VICTORIOSA RAINHA DOS CAMPOS: PONTA GROSSA NA CONJUNTURA REPUBLICANA (Revista de História Regional, 2007)
This article intends to establish a counterpoint between the over weening speech in Paraná, in the conjuncture of the Republic settlement, and the pessimism speech of the Catholic hierarchy. In the beggining of the 20th century, the city of Ponta Grossa, although presenting a rustic and timid urban profile, is seen by some intellectuals of the thime as a homelike, progressive urban area and appointed to be the capital of the centre of Paraná. From the bishopric pont of view, Paraná and Ponta Grossa were seen mission earth, the places where the Christian civilisation did not still arrive. In 1905, the stablishment of a feminine religious congregation - The Missionary Sisters Servas do Espírito Santo - in renewal moments of the Catholic institution, meant an attempt to the settlement of new guidelines of the the Roman chief church through education.